The Effect of Ethanol Extract of Cherry Tomato (Solanum lycopersicum L.) on Mast Cell Degranulation in Male White Mice Invitro - Relin Yesika; Meiridha Mutiara Andania; Rahmi Nurdi (LPPM Universitas Abdurrab, 2024)
Cherry tomatoes (Solanum lycopersicum L.) belong to the Solanaceae family which contains antioxidant compounds such as carotenoid compounds, which come from the terpenoid group, for example lycopene, besides cherry tomatoes also have flavonoid compounds. Both of these compounds have many pharmacological activities, one of which is as an anti-inflammatory. Inflammation starts from the process of mast cell degranulation, which is the process of releasing mast cell granules containing inflammatory mediators such as histamine, leukotriene and prostaglandins that cause type I hypersensitivity (allergies). This study aims to determine the effect of cherry tomato ethanol extract on mast cell degranulation of male white mice in vitro. The experimental animals used were male white mice that were actively sensitized after being induced with 20% ovalbumin antigen 0.2 mL/20 g BW on the first day intraperitoneally and the 7th day subcutaneously. The results of the average percentage of mast cell degranulation by cherry tomato extract at concentrations of 25 Î¼g/ml; 50 Î¼g/ml; 100 Î¼g/ml and 200 Î¼g/ml were 54.70%; 51.71%; 46.73%; 42.65% and 38.92%. This study shows that cherry tomato extract (Solanum lycopersicum L.) can inhibit mast cell degranulation in male white mice